THE RELATIONSHIP OF LIFESTYLE AND MENTAL HEALTH OF GENERATION Z : THE RELATIONSHIP OF LIFESTYLE AND MENTAL HEALTH OF GENERATION Z - M. Elyas Arif BUDIMAN; M. Faqih Ubaidillah Shaddam (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: The mental health of adolescents, especially generation Z, is a concern amidst social and technological changes. One of the factors that influence mental health is lifestyle. This study aims to determine the relationship between lifestyle and mental health of generation Z. Methods: This study used a cross-sectional approach with a correlational design. The population in this study were 243 nursing students from the 2021 intake at Dr. Soebandi University, Jember. The sample in this study consisted of 151 respondents using a cluster sampling method. Lifestyle was measured using a Likert scale questionnaire and mental health was measured using the SRQ-2 (Self-rating Questionnaire). Univariate analysis used frequency distribution and percentage, while bivariate analysis used Spearman's Rho Rank and correlation coefficient. Result: Most respondents' lifestyle (58.3%) is a high lifestyle, mental health of respondents (60.9%) is indicated mental health. The results of the Rank Spearman Rho analysis obtained p Vallue (0.00) ≤ (α) (0.05) means that Ha is accepted and H0 is rejected with a correlation coefficient value of -0.344 meaning a low relationship. Conclusion: There is a low relationship between lifestyle and mental health in generation Z. The higher the lifestyle, the lower the mental health in generation Z. Students are advised to adopt a balanced lifestyle, such as getting enough sleep, managing stress, and reducing the use of social media to maintain mental health